Activating atomically dispersed Co–N/C sites on g-C3N4 nanosheets via incorporating sulfur enables efficient visible light H2 evolution. Issue 1 (29th November 2021) - Wang, Fang; Xue, Yuan; Xu, Weibing; Min, Shixiong
Abstract : The inert Co–N/C sites on g-C3 N4 nanosheets (CNs) can be effectively activated via incorporating S for efficiently catalyzing visible light H2 evolution in a dye-sensitized system. Abstract : Embedding atomically dispersed metal (M)–N/C sites within two-dimensional (2D) g-C3 N4 nanosheets (CNs) is able to greatly improve charge separation efficiency; however, these sites are typically inert for catalyzing the photochemical H2 evolution reaction (HER). In this work, a simple room-temperature sulfurization strategy is proposed to activate the inert Co–N/C sites on CNs for efficiently catalyzing the dye-sensitized photocatalytic HER. By simply immersing cobalt-doped CNs (Co-CNs) into aqueous solution with high-concentration S 2−, the coordinated O atoms at Co–N/C sites are partially replaced by S atoms at room temperature, generating ample highly active S-coordinated Co–N/C sites with excellent dispersion preservation. The as-prepared S-Co-CNs catalysts exhibit enhanced activity in catalyzing the HER in an Erythrosin B–triethanolamine (ErB–TEOA) system under visible light irradiation, while both the pristine CNs and Co-CNs show negligible activity under the same reaction conditions. The most efficient S-Co-CNs catalyst achieves a H2 evolution rate of 6.38 mmol h −1 g −1 and a quantum efficiency (QE) of 13.02% at 520 nm, and this S-Co-CNs catalyst shows excellent HER stability when sensitized with a more stable fluorescein (FL) dye. The enhanced catalytic performance originates from the favorable electronic structure of the active sites adjusted by S modulation, leading to reduced H2 evolution overpotential while maintaining the favorable electron transfer kinetics. This work provides an effective strategy to activate inert sites embedded in CNs for high-performance photocatalytic water splitting, organic transformation, and CO2 reduction.